2013
DOI: 10.1007/s11222-013-9406-4
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage estimation of varying covariate effects based on quantile regression

Abstract: Varying covariate effects often manifest meaningful heterogeneity in covariate-response associations. In this paper, we adopt a quantile regression model that assumes linearity at a continuous range of quantile levels as a tool to explore such data dynamics. The consideration of potential non-constancy of covariate effects necessitates a new perspective for variable selection, which, under the assumed quantile regression model, is to retain variables that have effects on all quantiles of interest as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Let β̃ ( τ ) be the unpenanlized quantile regression estimator at level τ . When ω j ( τ ) = 1/(sup τ ∈Δ | β̃ ( j ) ( τ )|), the proposed estimator reduces to the UAL estimator (Peng et al, 2014). It can be shown that the classical adaptive weight, 1/| β̃ ( j ) ( τ )|, is also a qualified adaptive weight function.…”
Section: The General Adaptively Weighted Lasso Estimator For Varyinmentioning
confidence: 99%
See 2 more Smart Citations
“…Let β̃ ( τ ) be the unpenanlized quantile regression estimator at level τ . When ω j ( τ ) = 1/(sup τ ∈Δ | β̃ ( j ) ( τ )|), the proposed estimator reduces to the UAL estimator (Peng et al, 2014). It can be shown that the classical adaptive weight, 1/| β̃ ( j ) ( τ )|, is also a qualified adaptive weight function.…”
Section: The General Adaptively Weighted Lasso Estimator For Varyinmentioning
confidence: 99%
“…However, there still remains two important questions: (1) Is there a general type of adaptive weights to achieve oracle properties? (2) The numerical studies in Peng et al (2014) suggest that a BIC-type tuning parameter selector generally yields satisfactory rates of correct model identification. Is there any formal justification for the BIC-type selector?…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…proportional hazards, location shift effects) have been recognized. For example, variable selection based on these models may pose a considerable risk of missing variables that have complex, non-constant survival impact but are scientifically important (Peng et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…With p fixed, several authors also investigated the variable selection problem for CQR. For example, Shows et al (2010) and Peng et al (2014) proposed penalized estimating equations where censoring was handled by inverse probability weighting. Wang et al (2013) developed a robust variable selection method based on Wang and Wang (2009)’s work, adopting a global dimension reduction formulation to facilitate the local weight estimation.…”
Section: Introductionmentioning
confidence: 99%